Revisiting McGee’s Counterexample to Modus Ponens - Rubin, Mariela (2024)
In this paper, we provide a novel explanation of McGee’s (1985) alleged counterexample to Modus Ponens for indicative conditionals. Our strategy is to show that pragmatic phenomena interfere with intuitions concerning the acceptability of the inference. More specifically, we argue that two confounding factors at play affect our intuitions concerning the acceptability of the inference, neither of which is related to validity. First, the indefinite determiner phrase “a Republican” is ambiguous, to wit, it may receive either a specific or a non-specific reading (and as we shall see, substituting a disjunction or a definite description for the indefinite is of no help). Second, the conclusion triggers an ignorance inference concerning its antecedent. In light of this, we shall argue, McGee’s diagnosis must be rejected.